1992
DOI: 10.1103/physrevb.45.9
|View full text |Cite
|
Sign up to set email alerts
|

Orthopositronium study of positron-irradiation-induced surface defects in alumina powder

Abstract: Three-quantum-yield measurements and orthopositronium (o-Ps)-lifetime spectrometry at low temperatures are used to study the interaction of positronium with the surface in fine powders of aluminum oxide. It is found that electron and/or positron irradiation of the specimen induces surface defects which influence the positronium in three ways: (1) A surface positroniumlike bound state is created, (2) the fraction of o-Ps escaping from the particles is slightly inhibited, and (3) the escaped o-Ps is quenched in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Saito et al and other researchers also reported the spin conversion of Ps induced by surface paramagnetic centers in UV-and positron-irradiated fine oxide grains at low temperatures. [30][31][32] They studied the irradiation induced surface paramagnetic centers by ESR, and observed the increasing number of unpaired electrons with increasing irradiation time, which induces the spin conversion of Ps atoms.…”
Section: Xps and Esr Resultsmentioning
confidence: 98%
“…Saito et al and other researchers also reported the spin conversion of Ps induced by surface paramagnetic centers in UV-and positron-irradiated fine oxide grains at low temperatures. [30][31][32] They studied the irradiation induced surface paramagnetic centers by ESR, and observed the increasing number of unpaired electrons with increasing irradiation time, which induces the spin conversion of Ps atoms.…”
Section: Xps and Esr Resultsmentioning
confidence: 98%
“…Many studies on the interactions between Ps atoms and surfaces [1][2][3][4][5][6][7][8][9][10][11] have been done using aggregates of fine oxide grains that are suitable media to study the Ps-surface interactions. Recently, it has been shown by Dauwe et al 9,10 and by the present authors 11 that Ps atoms formed in the free space between oxide grains 12 react sensitively with irradiation-induced paramagnetic centers on the grain surfaces at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…These studies indicate usefulness of the positron annihilation techniques for the selective observation of the surface paramagnetic centers, since it is known that Ps atoms between the grains cannot penetrate back into the bulk region of the grains but interact with the surfaces only. [1][2][3][4][5][6][7][8] In previous works, [9][10][11] the positrons from ␤ ϩ sources were used both to form positronium, and to irradiate the sample. It was, therefore, difficult to control the irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray diffraction (XRD) spectra showed that after irradiation the X-ray peaks were only slightly shifted as compared to the non-irradiated samples, revealing the presence of stress but also that the crystal structure survived the irradiation, i.e., the disappearance of the long lifetime components cannot result from structural changes. A similar lifetime shortening in alumina powders due to irradiation was reported in [12] and it was ascribed to quenching of surface-bound o-Ps by irradiation-created interstitial atoms migrating to the surface. Similar effects were interpreted as a consequence of reaction with paramagnetic centers on the surfaces in SiO 2 [13] and in fine oxide grains [14].…”
Section: Resultsmentioning
confidence: 56%